Correlation Between the Severity of Coronary Heart Disease andQT Dispersion in Patients with Obstructive Sleep Apnea - Rasmijon, Rasmijon; Yamin, Muhammad; Hutauruk, Syahrial M.; Rumende, Cleopas Martin (Jurnal Penyakit Dalam Indonesia, 2019)
Introduction. Coronary heart disease (CHD) and obstructive sleep apnea (OSA) are common and complex clinical problems. Both have a high risk of sudden cardiac death (SCD). QT dispersion (QTd) in electrogram is a measure of heterogeneity of myocardial repolarization that can predict the occurrence of ventricular arrhythmias that cause SCD QTd is a predictor of ventricular arrhythmias and sudden cardiac death. So far, there is no publication about the severity relationship CHD with QTd in OSA patients in Indonesia. Methods. A cross-sectional study was conducted on twenty-nine CHD patients accompanied OSA in 2015 who had undergone coronary angiography and polysomnography against the QT dispersion by electrocardiography in Cipto Mangunkusumo Hospital, Jakarta. QTd obtained from maximum QTc difference with minimum QTc. The severity of CHD was assessed by the Gensini score obtained from the recording of coronary angiography in the cath lab. Results. The median value of Gensini score was 10 (range 1-112). Mean value of QTc max and QTc min were 459.76 ms (standard deviation [SD] 41.39 ms) and 386.72 ms (SD 31.61), respectively. Meanwhile, the median value of QTd was 56 ms (range 14-201 ms). The Spearman correlation test showed a weak positive correlation between Gensini score and QTd (r = 0.464; p value = 0.006). Conclusion. The severity of coronary heart disease by Gensini score is weakly correlated with QT dispersion.